2009
DOI: 10.1007/s10853-008-3010-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and humidity on electrospinning

Abstract: Electrospinning is a process that generates nanofibres. Temperature and humidity affect this process. In this article the influence of humidity and temperature on the formation and the properties of nanofibres are studied using cellulose acetate (CA) and poly(vinylpyrrolidone) (PVP) as target materials. The experiments indicate that two major parameters are dependent of temperature and have their influence on the average fibre diameter. A first parameter is the solvent evaporation rate that increases with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
300
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(341 citation statements)
references
References 15 publications
14
300
1
4
Order By: Relevance
“…The process parameters that were varied during electrospinning are the flow rate (0-2 mL/h), the tip to collector distance (TCD) (6-18 cm) and the applied voltage (0-30 kV). To minimize the effect of the ambient conditions (Medeiros et al 2008;De Vrieze et al 2008), all experiments were performed in a fume hood at room temperature (22 ± 2°C) and at a relative humidity of 45 ± 5 RH %, monitored by a Vaisala humidity probe. The morphology of the electrospun structures was examined using an FEI QUANTA 200 F Scanning Electron Microscope (SEM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process parameters that were varied during electrospinning are the flow rate (0-2 mL/h), the tip to collector distance (TCD) (6-18 cm) and the applied voltage (0-30 kV). To minimize the effect of the ambient conditions (Medeiros et al 2008;De Vrieze et al 2008), all experiments were performed in a fume hood at room temperature (22 ± 2°C) and at a relative humidity of 45 ± 5 RH %, monitored by a Vaisala humidity probe. The morphology of the electrospun structures was examined using an FEI QUANTA 200 F Scanning Electron Microscope (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…This allowed for the demarcation of a steady state region within the steady state table presenting the possible combinations of solvent ratio and polymer concentration for which a steady state is possible. This methodology has been used previously to verify the steady states for electrospinning different types of polyamides (De Vrieze et al 2008De Schoenmaker et al 2012) and polycaprolactones (Van der Schueren et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It was deduced that the increase in temperature reduces the viscosity of the solution and enhances the solvent evaporation, which results in thinner nanofibres [89]. Depending on the system under investigation, two antagonistic effects are observed: (1) reduction in fibre diameters, and (2) increase in diameter which may result in fusion of the nanofibres [90]. Tripatanasuwan et al [91] reported that an increase in relative humidity resulted in smaller diameters of the nanofibres.…”
Section: Ambient Conditionsmentioning
confidence: 99%
“…Os parâmetros ambientais, temperatura, umidade e composição do ar, também podem influenciar na formação e na morfologia das nanofibras [22,68,69] . Com este enfoque, Vrieze et al [68] estudaram o efeito da umidade ambiente e da temperatura na formação das nanofibras de acetato de celulose e PVP (polivinil pirrolidona).…”
Section: Parâmetros Ambientaisunclassified
“…Com este enfoque, Vrieze et al [68] estudaram o efeito da umidade ambiente e da temperatura na formação das nanofibras de acetato de celulose e PVP (polivinil pirrolidona). Os autores observaram que, para o PVP o aumento da umidade relativa resultou numa diminuição do diâmetro médio da fibra, enquanto que para o acetato de celulose o diâmetro médio da fibra aumentou.…”
Section: Parâmetros Ambientaisunclassified